2018
DOI: 10.14715/cmb/2018.64.11.16
|View full text |Cite
|
Sign up to set email alerts
|

Contrast enhanced ultrasound in diagnosis of endometrial carcinoma and endometrial hyperplasia

Abstract: The present study was aimed to compare application of contrast enhanced ultrasound (CEUS) in diagnosis of endometrial carcinoma (EC) and endometrial hyperplasia (EH). A total of 81 patients with EC and simple EH were selected in this study. Among all patients, 39 cases were diagnosed as EC and 42 cases were diagnosed with EH. All patients were diagnosed by CEUS examination. The diagnosis of EC and EH was also confirmed by endometrial biopsy. CEUS was conducted for all patients. Eendometrial thickness was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Endometrial carcinoma is the most common gynecological malignancy. 18 This is reflected in the higher number of studies evaluating CEUS for this malignancy: one case-control 17 and seven prospective cohort studies, 18,[20][21][22][23][24][25] with histology-proven endometrial carcinoma. These studies did show different enhancement patterns between malignant and healthy tissue.…”
Section: Contrast Ultrasound Enhancement Characteristics and Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Endometrial carcinoma is the most common gynecological malignancy. 18 This is reflected in the higher number of studies evaluating CEUS for this malignancy: one case-control 17 and seven prospective cohort studies, 18,[20][21][22][23][24][25] with histology-proven endometrial carcinoma. These studies did show different enhancement patterns between malignant and healthy tissue.…”
Section: Contrast Ultrasound Enhancement Characteristics and Quantificationmentioning
confidence: 99%
“…The average accuracy of CEUS as diagnostic tool for staging endometrial carcinoma is 81%, with an average sensitivity of 0.78 and specificity of 0.81. 17,18,[20][21][22][23][24][25] The numbers of the individual studies are shown in Table 3. The additional value of combined 2D-and 3D-CEUS imaging (diagnostic accuracy 84%) over 2D-CEUS alone (diagnostic accuracy 75%) was demonstrated in 68 patients with clinically suspected endometrial carcinoma, of which 26 cases were confirmed by histology.…”
Section: Contrast Ultrasound Enhancement Characteristics and Quantificationmentioning
confidence: 99%
“…The diagnosis of EC thus mainly depends on imaging, immunohistochemistry, pathology, and hysteroscopy [ 9 – 12 ]. At present, it is considered that transvaginal ultrasound measurement of endometrial thickness [ 9 , 13 , 14 ] and endometrial aspiration cytological examination are feasible technologies for EC screening. Dilatation and curettage [ 15 , 16 ] and hysteroscopy are also potentially effective screening methods, but are highly invasive and therefore not recommended.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of EC thus mainly depends on imaging, immunohistochemistry, pathology, and hysteroscopy [6,[14][15][16]. At present, it is considered that transvaginal ultrasound measurement of endometrial thickness [6][7][8] and endometrial aspiration cytological examination are feasible technologies for EC screening. Dilatation and curettage [9,10] and hysteroscopy are also potentially effective screening methods, but are highly invasive and therefore not recommended.…”
Section: Introductionmentioning
confidence: 99%